Preparation method and application of coconut shell fiber loaded with water-absorbent resin
By preparing coconut shell fibers loaded with water-absorbing resin, and then blending the water-absorbing resin with the coconut shell fibers and incorporating them into concrete, the shortcomings of using water-absorbing resin and coconut shell fibers alone are solved, achieving the dual effect of improving concrete strength and inhibiting shrinkage.
Patent Information
- Application Number
- CN202511161501.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-11-21
AI Technical Summary
In the existing technology, water-absorbing resin and coconut shell fiber each have their own problems when used alone. Excessive water-absorbing resin dosage will reduce the strength of concrete, and coconut shell fiber is prone to agglomeration, resulting in limited reinforcement effect. It is difficult to simultaneously improve the strength of concrete and inhibit drying shrinkage.
By preparing water-absorbing resin-loaded coconut shell fibers, the water-absorbing resin and coconut shell fibers are blended, and the blending is dried at 50-70℃ to prepare water-absorbing resin-loaded coconut shell fibers, which can be added to concrete to improve strength and inhibit drying shrinkage.
It achieves uniform dispersion of water-absorbing resin and coconut shell fiber, improves the strength of concrete and inhibits drying shrinkage, and synergistically improves the humidity environment and performance stability of concrete.
Smart Images

Figure CN120987587A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional material preparation technology for concrete, and in particular to a method for preparing and applying coconut shell fibers loaded with water-absorbing resin. Background Technology
[0002] In the concrete preparation process, how to improve the strength of concrete at low cost and inhibit its drying shrinkage cracking is a core problem that the industry urgently needs to solve.
[0003] In the prior art, superabsorbent polymers (SAPs) are used to improve the internal humidity environment of concrete due to their excellent water absorption and retention properties: after absorbing water, they form a "water reservoir" inside the concrete, and release water when the external free water decreases, which can reduce shrinkage, inhibit cracking and improve curing effect; however, excessive SAPs will reduce the strength of concrete, and after releasing water, they will leave tiny pores inside, which may affect the performance of concrete.
[0004] Coconut shell fiber, due to its hydrophilic groups such as cellulose and its micropores, also has a certain water retention capacity, good tensile strength, and strong adhesion to concrete, which can improve the mechanical properties of concrete to a certain extent; however, coconut shell fiber is prone to agglomeration in concrete, resulting in limited reinforcement effect.
[0005] Both water-absorbing resin and coconut shell fiber can cause problems when used alone. Water-absorbing resin contains a large number of carboxyl and hydroxyl groups, while coconut shell fiber contains hydroxyl groups; the two can adsorb each other through hydrogen bonds. Therefore, there is an urgent need for a technology that combines water-absorbing resin and coconut shell fiber to solve the problem of coconut shell fiber agglomeration, while simultaneously leveraging their synergistic water retention and reinforcing effects to achieve the dual benefits of increased concrete strength and shrinkage inhibition. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing and applying coconut shell fibers loaded with water-absorbing resin, in order to solve the above-mentioned problems.
[0007] This invention provides a method for preparing coconut shell fibers loaded with water-absorbing resin, comprising the following steps:
[0008] S1. Take the pretreated coconut shell fiber, soak it in water for at least 24 hours and then filter it, soak it in water for at least 2 hours and then filter it again to fully remove the leachate.
[0009] S2. Add water to the coconut shell fiber after step S1 to fully submerge the coconut shell fiber so that it can fully absorb water and drain the leachate.
[0010] S3. Add water-absorbing resin to the system in step S2. Stir the mixture after the water-absorbing resin has fully absorbed the water until the water-absorbing resin is attached to the surface of the coconut shell fibers and between the coconut shell fibers.
[0011] S4. Filter to remove moisture from the system to obtain a blend of coconut shell fiber and water-absorbing resin;
[0012] S5. The blend is dried at 50-70°C to obtain coconut shell fiber loaded with water-absorbing resin.
[0013] Preferably, in the above-mentioned method for preparing coconut shell fiber loaded with water-absorbing resin, in step S1, the diameter of the pretreated coconut shell fiber is 80μm-120μm and the length is 7mm-15mm.
[0014] Preferably, in the above-mentioned method for preparing coconut shell fiber loaded with water-absorbing resin, the pretreatment process of coconut shell fiber is as follows: after washing and drying the coconut shell fiber, it is cut to 20mm-50mm, black fiber nodules and residual coconut shell are removed by screening, and after grinding, it is cut to 7mm-15mm again, and finally fibers with a diameter of 80μm-120μm are screened out.
[0015] Preferably, in the above-mentioned method for preparing coconut shell fiber loaded with water-absorbing resin, in step S3, the particle size of the water-absorbing resin is 30-90 mesh.
[0016] Preferably, in the above-mentioned method for preparing coconut shell fiber loaded with water-absorbing resin, the 30-90 mesh water-absorbing resin is obtained by the following steps: the crude water-absorbing resin is shredded and washed with anhydrous ethanol at least 3 times, dried at 60°C and then ground into powder, then soaked in anhydrous ethanol to remove impurities and repeated at least 4 times, and then dried and passed through a 30-90 mesh sieve.
[0017] Preferably, in the above-mentioned method for preparing coconut shell fiber loaded with water-absorbing resin, in step S3, the mass ratio of the coconut shell fiber to the water-absorbing resin is 100:3.
[0018] Preferably, in the above-mentioned method for preparing coconut shell fiber loaded with water-absorbing resin, the drying temperature in step S5 is 60°C.
[0019] This invention provides a method for preparing loaded water-absorbing resin coconut shell fiber as described above, and the application of the prepared loaded water-absorbing resin coconut shell fiber in concrete. The loaded water-absorbing resin coconut shell fiber is incorporated into concrete to improve the strength of concrete and inhibit the drying shrinkage of concrete.
[0020] Preferably, in the above-mentioned application of water-absorbing resin-loaded coconut shell fiber, the water-absorbing resin-loaded coconut shell fiber is soaked in water for at least 24 hours before being incorporated into concrete.
[0021] Therefore, the present invention, by employing the above-described method for preparing and applying coconut shell fibers loaded with water-absorbing resin, has the following beneficial effects:
[0022] (1) In the preparation method, the water-absorbing resin and coconut shell fiber are first mixed together to make the two more evenly dispersed, so that some water-absorbing resin is attached to each coconut shell fiber, so that it has better dispersion performance after being added to concrete.
[0023] (2) After the water-absorbing resin is mixed with coconut shell fiber, the water-absorbing resin is adsorbed on the fiber, which disperses the coconut shell fiber that was originally entangled and agglomerated together, increases the distance between the coconut shell fiber, and reduces the physical adsorption force, electrostatic force and valence bond force between the coconut shell fiber. At the same time, since the water-absorbing resin is electronegative after absorbing water, the same water-absorbing resin repels each other, which in turn makes the fiber repel each other, so that the fiber is evenly dispersed in the solution. After being added to concrete, it can be better stirred and the fiber is more evenly dispersed.
[0024] (3) The strength of concrete after blending water-absorbing resin and coconut shell fiber was improved compared with the concrete strength tested with single water-absorbing resin, single coconut shell fiber, and double water-absorbing resin and coconut shell fiber. The water retention capacity of coconut shell fiber and the "water reservoir" effect of water-absorbing resin work synergistically to continuously improve the internal humidity environment of concrete and enhance the curing effect. At the same time, coconut shell fiber can compensate for the micropores left after the water-absorbing resin releases water, further ensuring the stability of concrete performance.
[0025] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0026] Figure 1 This is a schematic diagram of the preparation method and application embodiment of the coconut shell fiber loaded with water-absorbing resin according to the present invention;
[0027] Figure 2 This is a side view of a method for preparing and applying coconut shell fibers loaded with water-absorbing resin according to the present invention. Detailed Implementation
[0028] To better understand the above technical solutions, a detailed description of the solutions will be provided below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0029] The terminology used in the embodiments of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The singular forms “a,” “the,” and “the” as used in the embodiments of this invention and the appended claims are also intended to include the plural forms, and “multiple” generally includes at least two unless the context clearly indicates otherwise.
[0030] It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that an article or device that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such an article or device. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the article or device that includes said element.
[0031] This invention provides a method for preparing coconut shell fibers loaded with water-absorbing resin, comprising the following steps:
[0032] S1. Take the pretreated coconut shell fiber, soak it in water for at least 24 hours and then filter it, soak it in water for at least 2 hours and then filter it again to fully remove the leachate.
[0033] S2. Add water to the coconut shell fiber after step S1 to fully submerge the coconut shell fiber so that it can fully absorb water and drain the leachate.
[0034] S3. Add water-absorbing resin to the system in step S2. Stir the mixture after the water-absorbing resin has fully absorbed the water until the water-absorbing resin is attached to the surface of the coconut shell fibers and between the coconut shell fibers.
[0035] S4. Filter to remove moisture from the system to obtain a blend of coconut shell fiber and water-absorbing resin;
[0036] S5. The blend is dried at 50-70°C to obtain coconut shell fiber loaded with water-absorbing resin.
[0037] To further optimize the above technical solution, the pretreated coconut shell fibers have a diameter of 80μm-120μm and a length of 7mm-15mm.
[0038] To further optimize the above technical solution, the pretreatment process of coconut shell fiber is as follows: after washing and drying the coconut shell fiber, it is cut to 20mm-50mm, black fiber nodules and residual coconut shell are removed by screening, and after grinding, it is cut to 7mm-15mm again, and finally the fiber with a diameter of 80μm-120μm is screened out.
[0039] To further optimize the above technical solution, in step S3, the particle size of the water-absorbing resin is 30-90 mesh.
[0040] To further optimize the above technical solution, the 30-90 mesh water-absorbing resin is prepared by the following steps: the crude water-absorbing resin is shredded and washed with anhydrous ethanol at least 3 times, dried at 60°C and then ground into powder, then soaked in anhydrous ethanol to remove impurities and repeated at least 4 times, and then dried and passed through a 30-90 mesh sieve.
[0041] To further optimize the above technical solution, in step S3, the mass ratio of coconut shell fiber to water-absorbing resin is 100:3.
[0042] To further optimize the above technical solution, in step S5, the drying temperature is 60℃.
[0043] This invention provides a method for preparing loaded water-absorbing resin coconut shell fiber as described above, and the application of the prepared loaded water-absorbing resin coconut shell fiber in concrete. The loaded water-absorbing resin coconut shell fiber is incorporated into concrete to improve the strength of concrete and inhibit the drying shrinkage of concrete.
[0044] To further optimize the above technical solution, the coconut shell fiber loaded with water-absorbing resin is soaked in water for at least 24 hours before being incorporated into concrete.
[0045] To more clearly and in detail introduce the preparation method and application of the coconut shell fiber loaded with water-absorbing resin provided by the embodiments of the present invention, the following description will be based on specific embodiments.
[0046] Example 1
[0047] Weigh 5g of the pretreated fiber and place it in a cup. Soak in water for 24 hours, filter the leachate, and soak in water for another 2 hours. Filter to fully drain the leachate. Add water to 205g to ensure the coconut shell fiber is fully soaked, allowing it to absorb water and expel the leachate. Add 0.15g of absorbent resin with a particle size of 30-90 mesh to the cup. After the resin has fully absorbed water, stir with a stirring rod to mix thoroughly. Stop stirring when the absorbent resin adheres to both the coconut shell fiber and between the fibers. After thorough mixing, filter the water, retaining only the absorbent resin and coconut shell fiber blend. Place it in a drying room at 60℃. After the blend is completely dry, observe the adhesion of the absorbent resin using an ultra-high-resolution microscope. Figure 1 As shown, the coconut shell fiber product loaded with water-absorbing resin has been completed. 5.15g of the product was weighed and soaked in water for 24 hours before being added to cement to prepare test blocks for testing.
[0048] Comparative Example 1
[0049] A baseline group is set up, in which no materials are added to the cement.
[0050] Comparative Example 2
[0051] A single-admixture water-absorbing resin group is set up, in which the water-absorbing resin is added separately to the cement.
[0052] Comparative Example 3
[0053] A dual-component coconut shell fiber and water-absorbing resin group is set up, in which coconut shell fiber and water-absorbing resin are simultaneously incorporated into cement.
[0054] Strength tests were conducted on the products to compare the effects of loading water-absorbing resin onto coconut shell fibers. The test formulations are shown in Table 1 below.
[0055] Table 1 Strength Test Mix Ratio
[0056]
[0057]
[0058] A 40mm×40mm×160mm triple-mold specimen was prepared and left to solidify for 1 day. Afterward, the specimen was removed from the mold and placed in a curing chamber for 7 days. The flexural and compressive strengths of the specimens were tested after 28 days. The test results are shown in Table 2 below.
[0059] Table 2 Strength Test / MPa
[0060]
[0061] A drying shrinkage test was conducted on the product to compare the effect of loading water-absorbing resin onto coconut shell fibers. The test formulation is shown in Table 3 below.
[0062] Table 3 Shrinkage Test Ratio
[0063]
[0064]
[0065] Cylindrical drying shrinkage specimens were prepared and left to solidify for 1 day. Afterward, they were demolded and placed in a curing room for another 1 day of curing before the drying shrinkage test. Before the test, both ends of the 1-day cured cylindrical specimens were sealed with sealing tape, leaving only the sides exposed to ensure one-dimensional moisture transfer within the specimen. Three drying shrinkage specimens were prepared for each formulation. The effective length for the drying shrinkage test was 20 cm. The prepared specimens were placed in the laboratory, and a connecting shrinkage test mold was constructed. Each specimen was tested using two dial gauges, and the dial gauge readings were recorded. The experimental value was the average of the two dial gauge readings. After the specimens were prepared, the effective length and the dial gauge reading d0 were recorded. The dial gauge reading d0 was then recorded daily. n The temperature and humidity were measured daily, and the dial gauge readings were recorded for 6 days, 8 days, 10 days, 12 days, 14 days, 15 days, 45 days, 60 days, 70 days, 90 days, 120 days, and 150 days. The final test results are shown in Tables 4 and 5. Tables 6 and 7 are the temperature and humidity recording tables. The shrinkage test chart is shown below. Figure 2 As shown.
[0066] Table 4 Shrinkage Amount from Shrinkage Test
[0067]
[0068]
[0069] Table 5 Shrinkage amount from shrinkage test
[0070]
[0071] Table 6 Shrinkage Test Temperature and Humidity Table
[0072] sky 1 2 3 4 5 6 8 10 12 temperature 20 21 20 18 18 18 18 18 18 humidity 28 27 22 23 23 23 23 23 23
[0073] Table 7 Shrinkage Test Temperature and Humidity Table
[0074] sky 14 15 45 60 70 90 120 150 temperature 18 18 18 19 21 21 23 24 humidity 25 25 24 33 31 41 44 39
[0075] As shown in Table 2, the tensile and compressive strengths of the cement specimens in Example 1 loaded with water-absorbing resin and coconut shell fiber were higher than those in Comparative Example 3, which combined coconut shell fiber and water-absorbing resin. This indicates that loading with water-absorbing resin and coconut shell fiber is beneficial to the development of concrete strength and makes it more uniformly dispersed in the concrete after loading. The compressive strength of the cement specimens in Example 1 and Comparative Example 3 was higher than that in Comparative Example 2, which combined water-absorbing resin alone. This indicates that the addition of coconut shell fiber has a good effect on improving the compressive strength of concrete. The flexural strength of the single-admixture water-absorbing resin group was higher than that of the baseline group in Comparative Example 1. The single-admixture water-absorbing resin group improved the toughness of concrete, but the improvement in compressive strength was not significant. After adding water-absorbing resin and coconut shell fiber, the 28-day compressive strength increased by 19.6% and the flexural strength increased by 4.3% compared to the baseline group. Compared to the double-admixture coconut shell fiber and water-absorbing resin group in Comparative Example 3, the compressive strength of the cement specimens in Example 1 loaded with water-absorbing resin and coconut shell fiber increased by 9.9% and the flexural strength increased by 7.4%. Coconut shell fibers loaded with water-absorbing resin are more evenly dispersed in concrete, and the effect of loading on improving concrete performance is more obvious.
[0076] From contraction Figure 2 It can be seen that the shrinkage of cement specimens in Examples 1, 2, and 3 is less than that of the cement specimens in the baseline group of Comparative Example 1. Furthermore, the shrinkage amounts of the three are similar. Compared to the 0.1908 shrinkage of the baseline group of Comparative Example 1, the shrinkage suppressed by Examples 1, 2, and 3 is 0.0233, 0.0208, and 0.0255, respectively. The shrinkage of cement specimens in Example 1 with added water-absorbing resin and coconut shell fiber and Comparative Example 2 with only water-absorbing resin are similar, and both show a decrease compared to the baseline group of Comparative Example 1. This indicates that the addition of both water-absorbing resin and coconut shell fiber has the effect of inhibiting shrinkage, and the addition of coconut shell fiber does not affect the shrinkage of the water-absorbing resin.
[0077] Therefore, this invention employs the aforementioned method for preparing and applying coconut shell fibers loaded with water-absorbing resin. In the preparation method, the water-absorbing resin and coconut shell fibers are first blended to achieve more uniform dispersion, ensuring that each coconut shell fiber is coated with some water-absorbing resin. This results in better dispersion performance when incorporated into concrete. After blending the water-absorbing resin with the coconut shell fibers, the resin adsorbs onto the fibers, dispersing the previously tangled and clustered fibers. This increases the distance between the fibers, reducing the physical adsorption force, electrostatic force, and valence bond force between them. Simultaneously, because the water-absorbing resin becomes electronegative after absorbing water, similar resins repel each other, leading to fiber repulsion. This ensures the fibers are uniformly dispersed in the solution, resulting in better mixing and more uniform fiber dispersion when incorporated into concrete. The strength tested after incorporating the water-absorbing resin and coconut shell fiber blend into concrete is higher than that tested with single-component water-absorbing resin, single-component coconut shell fiber, and double-component water-absorbing resin and coconut shell fiber. The water retention capacity of coconut shell fiber and the "water reservoir" function of water-absorbing resin work synergistically to continuously improve the internal humidity environment of concrete and enhance the curing effect. At the same time, coconut shell fiber can compensate for the tiny pores left after the water-absorbing resin releases water, further ensuring the stability of concrete performance.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing coconut shell fibers loaded with absorbent resin, characterized in that, Includes the following steps: S1. Take the pretreated coconut shell fiber, soak it in water for at least 24 hours and then filter it, soak it in water for at least 2 hours and then filter it again to fully remove the leachate. S2. Add water to the coconut shell fiber after step S1 to fully submerge the coconut shell fiber so that it can fully absorb water and drain the leachate. S3. Add water-absorbing resin to the system in step S2. Stir the mixture after the water-absorbing resin has fully absorbed the water until the water-absorbing resin is attached to the surface of the coconut shell fibers and between the coconut shell fibers. S4. Filter to remove moisture from the system to obtain a blend of coconut shell fiber and water-absorbing resin; S5. The blend is dried at 50-70°C to obtain coconut shell fiber loaded with water-absorbing resin.
2. The method for preparing coconut shell fiber loaded with water-absorbing resin according to claim 1, characterized in that, In step S1, the pretreated coconut shell fibers have a diameter of 80μm-120μm and a length of 7mm-15mm.
3. The method for preparing coconut shell fiber loaded with water-absorbing resin according to claim 2, characterized in that, The pretreatment process of coconut shell fiber is as follows: After washing and drying the coconut shell fiber, it is cut to 20mm-50mm, black fiber nodules and residual coconut shell are removed by screening, and after grinding, it is cut to 7mm-15mm again. Finally, fibers with a diameter of 80μm-120μm are screened out.
4. The method for preparing coconut shell fiber loaded with water-absorbing resin according to claim 1, characterized in that, In step S3, the particle size of the absorbent resin is 30-90 mesh.
5. The method for preparing coconut shell fiber loaded with water-absorbing resin according to claim 4, characterized in that, The 30-90 mesh water-absorbing resin is prepared by the following steps: the crude water-absorbing resin is shredded and washed with anhydrous ethanol at least 3 times, dried at 60°C and then ground into powder, then soaked in anhydrous ethanol to remove impurities and repeated at least 4 times, and then dried and passed through a 30-90 mesh sieve.
6. The method for preparing coconut shell fiber loaded with water-absorbing resin according to claim 1, characterized in that, In step S3, the mass ratio of coconut shell fiber to water-absorbing resin is 100:
3.
7. The method for preparing coconut shell fiber loaded with water-absorbing resin according to claim 1, characterized in that, In step S5, the drying temperature is 60°C.
8. The application of the water-absorbing resin-loaded coconut shell fiber prepared by the method for preparing water-absorbing resin-loaded coconut shell fiber according to any one of claims 1-7 in concrete, characterized in that, The loaded water-absorbing resin coconut shell fiber is incorporated into concrete to improve its strength and inhibit its drying shrinkage.
9. The application of coconut shell fiber loaded with water-absorbing resin according to claim 8, characterized in that, The coconut shell fiber loaded with water-absorbing resin is soaked in water for at least 24 hours before being incorporated into concrete.